SNHG17 Serves as an Oncogenic lncRNA by Regulating the miR-361-3p/STC2 Axis in Rectal Cancer - Huang, Fuda; Li, Hua; Qin, Zebang; Wang, Anmin; Zhang, Ya; Guo, Junyu; Wei, Mingwei; Guo, Houji; Pu, Jian (Frontiers in Genetics, 2021)
Long noncoding RNA (lncRNA) has been reported to be crucial regulators for cancer carcinogenesis, including rectal cancer. Small nucleolar RNA host gene 17 (SNHG17) has been reported to be crucial regulators for cancer pathogenesis. In this work, we aimed to explore the roles and associated mechanisms of SNHG17 in rectal cancer progression. Quantitative real-time polymerase chain reaction was performed to measure expression level of SNHG17 in rectal cancer tissues and cells. Cell counting kit-8 assay, and flow cytometry assay were conducted to measure the functions of SNHG17 in rectal cancer. In addition, luciferase activity reporter assay, RNA immunoprecipitation assay, and rescue experiments were conducted to explore the potential mechanisms of SNHG17. Upregulation status of lncRNA-SNHG17 was identified in rectal cancer tissues and cells. Functionally, force the expression of SNHG17 stimulates rectal cancer cell proliferation. In vivo assay showed that knockdown of SNHG17 inhibits tumor growth. Furthermore, we showed microRNA-361-3p (miR-361-3p) was decreased expression in tumor tissues and cells, and SNHG17 functions as a sponge for miR-361-3p. Besides that, upregulation status of stanniocalcin 2 (STC2) was also found in rectal cancer, and the knockdown of STC2 hinders cancer progression. In conclusion, lncRNA SNHG17 functions as an oncogenic lncRNA in rectal cancer by regulating miR-361-3p/STC2 axis.